Involuntary career transition and identity within the artist population - Hennekam, S.; Bennett, Dawn (Emerald, 2016)
Purpose – The purpose of this paper is to examine artists’ experiences of involuntary career transitions and its impact on their work-related identities. Design/methodology/approach – Semi-structured interviews with 40 artists in the Netherlands were conducted. Self-narratives were used to analyze the findings. Findings – Artists who can no longer make a living out of their artistic activities are forced to start working outside the creative realm and are gradually pushed away from the creative industries. This loss of their creative identity leads to psychological stress and grief, making the professional transition problematic. Moreover, the artistic community often condemns an artist’s transition to other activities, making the transition psychologically even more straining. Originality/value – This study provides in-depth insights into how artists deal with changes in their work-related identities in the light of involuntary career transitions.